1970
DOI: 10.3329/bjar.v34i3.3961
|View full text |Cite
|
Sign up to set email alerts
|

Growth and yield components of wheat genotypes exposed to high temperature stress under control environment

Abstract: High temperature stress during grain-filling period is one of the major environmental constraints limiting the grain yield of wheat in Bangladesh. Crop growth response and relative performance of yield components of ten wheat genotypes were studied in two temperature conditions in glass rooms in a Phytotron to identify the genotype tolerant to high temperature stress. A favourable day/night temperatures of 15/10, 20/15, and 25/20 0 C were maintained from sowing to 60 days after sowing (DAS), 61 to 80 DAS and 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
52
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(60 citation statements)
references
References 25 publications
7
52
0
1
Order By: Relevance
“…The cellular injury is evaluated by measuring the leakage of electrolytes in order to assess the severity of existing stress (Savicka and Škute, 2010). Membrane stability is positively related to yield performance under HS stress (Rahman et al, 2009). To repair the inhibitory effects of ROS, plants make use of antioxidant defense machinery that includes enzymatic and non-enzymatic antioxidant system that is involved in the detoxification of ROS.…”
Section: Introductionmentioning
confidence: 99%
“…The cellular injury is evaluated by measuring the leakage of electrolytes in order to assess the severity of existing stress (Savicka and Škute, 2010). Membrane stability is positively related to yield performance under HS stress (Rahman et al, 2009). To repair the inhibitory effects of ROS, plants make use of antioxidant defense machinery that includes enzymatic and non-enzymatic antioxidant system that is involved in the detoxification of ROS.…”
Section: Introductionmentioning
confidence: 99%
“…Elevated temperature induces pollen sterility and seed abortion, resulting in lower seed weight, and also significantly affects flour yield and dough quality (Hays et al 2007;Altenbach 2012). High temperature accelerates flowering and grain maturity, which is paralleled by reduced crop height, leaf growth and number of tillers per plant (Rahman et al 2009;Zhang et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…However, water use efficiency was highest when less irrigation was applied. Poor performance of these growth parameters in elevated temperature may be due to enhanced leaf senescence and growth retardation (Rehman et al, 2009) during growth phase, while it was recorded that as water plays its substantial role in cell division and elongation, ultimately in growth so restricted cell division and expansion (Alves and Setter, 2004) and more rate of leaf senescence (Hafsi et al, 2000) was reported due to water stress ( Table 2). The significantly different periodic trend regarding LAI, LAD and CGR under temperature regimes and irrigation levels is also elaborated in pictorial representation (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Among the abiotic stresses, heat stress is one of the major abiotic stress which results in linear yield decline in many crops (Hays et al, 2007). Heat stress negatively influences the plant growth and development resulting in reduced plant leaf area, less growth, early leaf senescence, less number of productive tillers per plant (Rehman et al, 2009), abnormal embryo formation (Saini et al, 2010), pollen mortality, (Saini et al, 2010), grain abortion (Hays et al, 2007), reduced grain weight and grain number per spike (Schapendonk et al, 2007), resulting in lower crop yield. Like heat, drought is also one of the main factors limiting the productivity of many crops across the globe (Xing et al, 2009).…”
Section: Introductionmentioning
confidence: 99%